The Blue Lotus Flower (Nymphea caerulea) Resin Used in a New Type of Electronic Cigarette, the Re-Buildable Dripping Atomizer. Issue 3 (27th May 2017) - Poklis, Justin L.; Mulder, Haley A.; Halquist, Matthew S.; Wolf, Carl E.; Poklis, Alphonse; Peace, Michelle R.
ABSTRACT: The blue lotus flower ( Nymphea caerulea ) is an Egyptian water lily containing apomorphine and nuciferine. Apomorphine has been described as a psychoactive alkaloid and is a non-selective dopamine agonist primarily used to treat Parkinson's disease as it stimulates dopamine receptors and improves motor function. Nuciferine is an alkaloid associated with dopamine receptor blockade. Today, blue lotus flower is used as a sleep aid and anxiety reliever. The rebuildable dripping atomizer (RDA) is an electronic cigarette that allows direct application of an e-liquid onto the coil in the atomizer for aerosolization, compared to a typical electronic cigarette where the e-liquid is wicked from a storage vessel to the coil. Our laboratory received a dark-brown resin material from a concerned parent. The resin had been confiscated from an adolescent who had a reported history of marijuana use. The resin was later identified as blue lotus flower ( N. caerulea ). This resin, together with four commercially available blue lotus products, was analyzed for content. Apomorphine was detected in two samples, and nuciferine was detected in all five samples. The confiscated resin was determined to contain no apomorphine and 4300 ng/g of nuciferine. The nuciferine resin was shown to aerosolize using aRDA electric cigarette.